TANDA ROFA’ WAWU DAN PENGARUHNYA TERHADAP AKHLAK SEORANG MUSLIM - Siti Rahimah Harahap; Ayu Sekarsari (Jurnal Shaf, 2025)
This study examines the use of the rofa’ marker wawu in Arabic from linguistic, philosophical, and moral perspectives that are relevant to the formation of a Muslim’s character. Using a qualitative approach through library research, the study analyzes both classical and contemporary literature on the use of wawu as a nominative marker in jama’ mudzakkar salim and asma’ul khamsah. The findings reveal that wawu as a grammatical indicator not only reflects structural syntax but also conveys symbolic values representing social order, semantic stability, and respect for noble social relationships. As a rofa’ marker, wawu functions as a symbol of honor within the linguistic and spiritual context of Islam. This research positions nahwu (Arabic grammar) not merely as a technical linguistic tool, but as a means of character education and spiritual development. Thus, Arabic grammar instruction can serve to instill moral values such as responsibility, discipline, and reverence for social roles. This interdisciplinary approach broadens the understanding of Arabic as an ethical medium that shapes a morally upright and spiritually aware Muslim identity.